Analysis of HIF2α polymorphisms in infertile women with polycystic ovary syndrome or unexplained infertility - Zheng, Xiaoya; Ma, Jiani; Hu, Min; Long, Jian; Wei, Qiang; Ren, Wei (Frontiers in Endocrinology, 2022)
Objective: To evaluate HIF2α polymorphisms and glucose metabolism in a group of women with polycystic ovary syndrome (PCOS) or unexplained infertility (UI). Patients: The infertile group (n=148) consisted of 96 women with PCOS, 52 women with UI, and176 women without infertility as a healthy control group. Intervention: We genotyped 29 single nucleotide polymorphisms (SNPs) of HIF2α by using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS)-based genotyping technology. The genetic associations were analyzed statistically. Main Outcome Measures: Allele frequency, genotype distribution and haplotype analyse of the HIF2α polymorphisms were performed. Body mass index (BMI), waist circumference, uric acid (UA), high-sensitivity C-reactive protein (hsCRP), lipids, glucose and insulin tolerance - were also measured. Results: Infertile women with PCOS had a higherBMI and waist circumference, elevated hsCRP and uric acid (UA) levels, impaired glucose tolerance, and increased levels of plasma insulin compared to UI patients and healthy women. SNP analysis of HIF2α revealed that the allele and genotype frequencies of rs4953361 were significantly associated with infertile women with PCOS. Haplotype analysis of the HIF2α polymorphism identified haplotypes TGG and TGA as being associated with infertile women with PCOS. Women with the AA genotype of rs4953361 had a significantly higher BMI and postload plasma glucose and insulin levels than those of women with the GG genotype. Conclusion: Infertile women with PCOS more commonly have metabolic disturbances than those with UI. This is the first study to report an association between HIF2α polymorphisms (rs4953361) and the risk of infertile women with PCOS, not UI, in Han Chinese population. These results require replication in larger populations.